Apolipoprotein E alleles in women with severe pre-eclampsia. Issue 4 (April 1998) - Nagy, B; Rigó, J; Fintor, L; Karádi, I; Tóth, T
Abstract : This study investigated the frequency of apolipoprotein E (apoE) alleles among women with severe pre-eclampsia. The presence of the three most common apoE alleles (epsilon 2, epsilon 3, epsilon 4) was determined by polymerase chain reaction-restriction fragment length polymorphism in three groups of white women: non-pregnant healthy (n = 101), pregnant healthy (n = 52), and pregnant with a diagnosis of severe pre-eclampsia (n = 54). The frequency of apo epsilon 2 was highest among women with severe pre-eclampsia (16.6%) followed by non-pregnant women (12.9%), and those experiencing a healthy pregnancy (10.6%). The higher frequency of the apo epsilon 2 allele detected among women with severe pre-eclampsia suggests that apoE may play a role in the development of pre-eclampsia.